Studying the impact of a medication use evaluation for polymedicated older patients by the community pharmacist (SIMENON): study protocol - J. Wuyts; J. Maesschalck; I. De Wulf; K. Foubert; K. Boussery; J. De Lepeleire; V. Foulon (BMC, 2018)
Abstract Background Aged polymedicated patients are particularly vulnerable for drug-related problems. A medication review aims to optimize the medication use of patients and improve health outcomes. In this study, the effect of a pharmacist-led medication use review is investigated for polymedicated ambulatory older patients with the aim of implementing this pharmaceutical care intervention across Belgium. Methods This article describes the study protocol of the SIMENON study and reports the results of the feasibility study, which aimed to test and optimize this study protocol. In the SIMENON intervention study, 75 Belgian community pharmacies each recruit 12 patients for a medication use review. For each patient, the identified drug-related problems and subsequent interventions are registered using the PharmDISC classification. In a subset of Dutch speaking patients, a pretest-posttest single group design is used to measure the impact of this review on patient related outcomes using questionnaires. The main outcome of the study is the type and number of drug-related problems and related interventions. A second outcome is the impact of the medication use review on adherence, objectively measured with dispensing data. Evolution in medication related quality of life is another outcome, measured with the Living with Medicines Questionnaire version 3. Other patient reported outcomes include adherence, self-management, patient satisfaction, fall incidents and use of emergency healthcare services. Discussion The findings of this study can provide data on the effectiveness of a medication use review in the Belgian primary care setting. Furthermore, it will provide insights in which patients benefit most of this intervention and therefore facilitate the implementation of medication review in Belgium. Trial registration ClinicalTrials.gov NCT03179722. Retrospectively registered 7 June 2017.